Urban Development Strategies for Resilient and Sustainable European Cities. Concluding Remarks to the Special Issue. - Kurth, Detlef (Taylor & Francis, 2020)
The corona virus started spreading worldwide in early 2020. In the last 12 months, the pandemic has reshaped the world. Its consequences for urban development are still unclear. So far, it is quite obvious that the lockdown and the pandemic crisis management will have a strong impact on the socio-economic development − especially in cities − and will accelerate digitization. Like in a burning glass, this pandemic makes visible long existing problems in urban development and forces us to face unresolved problems of sustainable urban development. In this contribution we give sketches of possible consequences of this crisis on cities and city-regions.
Keywords: Stadtentwicklung; Stadtregion; Entwicklungsperspektive; Digitalisierung; Nachhaltige Stadtentwicklung; Krisensituation; Katalysator; Corona-Krise